2016
DOI: 10.1038/nature18298
|View full text |Cite|
|
Sign up to set email alerts
|

Structural basis of N6-adenosine methylation by the METTL3–METTL14 complex

Abstract: Chemical modifications of RNA have essential roles in a vast range of cellular processes. N(6)-methyladenosine (m(6)A) is an abundant internal modification in messenger RNA and long non-coding RNA that can be dynamically added and removed by RNA methyltransferases (MTases) and demethylases, respectively. An MTase complex comprising methyltransferase-like 3 (METTL3) and methyltransferase-like 14 (METTL14) efficiently catalyses methyl group transfer. In contrast to the well-studied DNA MTase, the exact roles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
1,020
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 936 publications
(1,059 citation statements)
references
References 36 publications
38
1,020
0
1
Order By: Relevance
“…Given the inherent AdoMet binding pocket of METTL3 (Wang et al, 2016a; Wang et al, 2016b), we next examined whether METTL3 directly interacts with methylated mRNA. Using a synthesized 30 nt mRNA with or without a single m 6 A site at the consensus sequence, we conducted a gel-shifting assay.…”
Section: Resultsmentioning
confidence: 99%
“…Given the inherent AdoMet binding pocket of METTL3 (Wang et al, 2016a; Wang et al, 2016b), we next examined whether METTL3 directly interacts with methylated mRNA. Using a synthesized 30 nt mRNA with or without a single m 6 A site at the consensus sequence, we conducted a gel-shifting assay.…”
Section: Resultsmentioning
confidence: 99%
“…The most striking parallel with the prozyme paradigm emerged from the work on the human RNA methyltransferase complex METTL3-METTL14. In this complex, METTL3 constitutes the catalytic core and binds AdoMet but requires allosteric activation and stabilization by METTL14 (48,49). Although METTL14 has been reported to exhibit weak in vitro methylation activity (50), the phylogenetic analysis suggests that the METTL14 catalytic core has lost its function (51).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, purified METTL14 manifested methyltransferase activities [10,20], suggesting that METTL14 is a distinct m 6 A writer. However, recent independent crystallization studies [22][23][24] demonstrated that METTL3, not METT14, bound to SAM and catalyzed m 6 A formation. Based on crystal structure analysis of METTL3-METTL14 complex, METTL14 possessed a degenerated SAM-binding domain, which was not functional.…”
Section: Mettl14mentioning
confidence: 99%